LEGAL EDUCATION IN PREVENTING CRIME AMONG TODAY'S YOUTH - pcadmin, Ibragimov Shukhrat Isroilovich (Scholar Express Journal, 2025)
The role of legal education in preventing crimes among today's youth is incomparable. Through legal education, young people understand their rights and duties and try to avoid negative behavior. This process develops the legal culture of young people and educates them as socially responsible and disciplined citizens. Legal education also helps prevent crimes and social problems, and protects young people from negative influences.
Keywords: Youth; legal education; delinquency